RAMADHAN: BLESS OR DISGRACE? - Raharjo, Agus (Jurnal Dinamika Hukum, 2018)
In Ramadhan 1439 H/2018 M, Islamic preacher said that Ramadan as a month full of blessing, forgiving, month of knowledge, another spell that lead Moslem people to act wisely. Nowadays, two important events came as government mirror. Both of them occurred in mass media even debated either social or electronic media......